2017
DOI: 10.4995/reinad.2017.6503
|View full text |Cite
|
Sign up to set email alerts
|

Trayectoria delictiva y factores de riesgo de los menores que ejercen violencia filioparental

Abstract: ResumenEn los últimos años, en los medios de comunicación han aumentado alarmantemente los casos de lo que parece un nuevo y preocupante fenómeno de violencia doméstica: la violencia filio-parental. De esta forma, el objetivo del presente trabajo es analizar la trayectoria delictiva y los factores de riesgo de los/as menores que han cometido violencia filio-parental en función del sexo. Los participantes de este estudio son 57 menores del Juzgado de Castellón (34 chicos y 23 chicas), cuyo rango de edad oscila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 4 publications
(2 reference statements)
3
8
0
Order By: Relevance
“…However, less attention has been paid to the school variables. In fact, in the meta-analyses regarding this topic made by Aroca, Lorenzo and Miró [10], Holt [1] and Martínez, Estévez, Jiménez and Velilla [11], it is observed that the school environment, together with the community, is the one that has received less attention despite being a context of great importance for the development of young people, where behavioral and academic difficulties can appear, but also resources for intervention [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, less attention has been paid to the school variables. In fact, in the meta-analyses regarding this topic made by Aroca, Lorenzo and Miró [10], Holt [1] and Martínez, Estévez, Jiménez and Velilla [11], it is observed that the school environment, together with the community, is the one that has received less attention despite being a context of great importance for the development of young people, where behavioral and academic difficulties can appear, but also resources for intervention [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The total score provides a recidivism risk level for him/ her, which can be classified as low (from 0 to 8 points), moderate (from 9 to 22), high (from 23 to 32) and very high (from 33 to 42). The YLS/CMI has shown satisfactory psychometric properties in previous studies, obtaining a Cronbach's alpha ranging from .56 to .91 (Catchpole & Gretton, 2003;Cuervo et al, 2017;Rodgers & Rowe, 2002;Schmidt et al, 2002;Thompson & Putnins, 2003) for all the items. In this study, the Cronbach's alpha was .87.…”
Section: Instrumentmentioning
confidence: 90%
“…These differences are larger in general samples of juvenile offenders, in which the percentage is around 80% and 90% for males, and around 10% and 20% for females (INE, 2020;Ortega-Campos et al, 2016;Van der Put & de Ruiter, 2016;Verbruggen et al, 2016). For age, research on CPV in Spain shows a majority of juveniles between 15 and 16 years old who commit CPV (Cuervo et al, 2017;Garc ıa & Cerezo, 2017;Loinaz et al, 2020), while international studies place the age range for these minors at between 16 and 17 years old (Armstrong et al, 2018;Ulman & Straus, 2003), and the same applies to general samples of juvenile offenders (INE, 2020;Ortega-Campos et al, 2016;Van der Put & de Ruiter, 2016;Verbruggen et al, 2016). In fact, antisocial behavior usually starts by the age of 13 years, increases until 17 years and finally decreases (Loeber et al, 2011;Moffitt, 1993Moffitt, , 2007Olver et al, 2012;Verbruggen et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations